Peningkatan Hasil Belajar Siswa dalam Menyelesaikan Soal Pecahan Melalui Penerapan Model Pembelajaran STAD Dikelas 6 SDN 104202 Bandar Setia Medan - Nur Wahyuni; Diah Anita Hasibuan (Lembag, 2025)
This study aimed to improve the learning outcomes of sixth-grade students at SDN 104202 Bandar Setia Medan in solving fraction problems through the application of the STAD learning model. This research is classroom action research (CAR) conducted in two cycles. The research subjects were 25 sixth-grade students at SDN 104202 Bandar Setia Medan. Data collection instruments included student learning outcome tests and observations of student learning activities. The results showed a significant improvement in student learning outcomes after the implementation of the STAD learning model. In cycle I, the average student score was 65, increasing to 78 in cycle II. Student learning activities also increased, as indicated by the increased participation of students in group discussions and presentations of group work. The application of the STAD learning model proved effective in improving student learning outcomes in solving fraction problems. This is because the STAD learning model encourages students to collaborate, discuss, and help each other in understanding the concept of fractions. In addition, the element of competition between groups also motivates students to study harder. This research recommends that the STAD learning model can be applied in mathematics learning in elementary schools to improve student learning outcomes, especially in fraction materials. Further research can investigate the application of the STAD learning model on other mathematics materials or at different educational levels.